Gravitational Electromagnetic Confinements: A Novel Framework challenging “General Relativity” through “Light and Gravity Interactions” (JOURNAL OF ADVANCES IN PHYSICS, 2025)
In the field of astronomy and astrophysics, the profound relationships between black holes, dark matter, and the complex interactions of light, gravity, and electromagnetic forces continue to captivate scientists. Building on Einstein's General Relativity, which describes spacetime curvature influenced by gravitational fields and supports the constancy of light speed in a vacuum, a new perspective is emerging. This fresh viewpoint proposes an "Equilibrium" concept regulating the five fundamental force densities in light, suggesting that light speeds can dynamically vary when coherent laser beams intersect. This idea deviates from the long-held assumption of a constant light speed, challenging General Relativity's core principles and prompting an investigation into gravitational and light interactions at both cosmic and microscopic levels. This research spans a variety of phenomena, including gravitational redshift, black holes, dark matter, and the microscopic processes of light absorption and emission. Unlike the established framework of General Relativity, this innovative perspective aims to bridge gravity and light through a melding of the Stress-Energy Tensor and the Gravitational Tensor. This union elucidates the interplay between gravity and electromagnetism and introduces a new tensor representation for black holes, called Gravitational Electromagnetic Confinements. By incorporating electromagnetic energy gradients and Lorentz transformations, this approach extends beyond the traditional bounds of General Relativity, especially in gravitational lensing scenarios. Reinterpreting Einstein's foundational work with the Einstein Gravitational Constant within the Energy-Stress Tensor forms a combined Electromagnetic and Gravitational Tensor framework. Theoretical advancements in black hole solutions echo the pioneering spirit of John Archibald Wheeler’s 1955 work, offering critical solutions for the relativistic quantum mechanical Dirac equation within a tensor format. Experimental validation of this paradigm, using data from Galileo Satellites and ground-based MASER frequency measurements, highlights discrepancies between General Relativity and the proposed new theory, enhancing gravitational observations to new levels of precision. The intersection of Quantum Physics and General Relativity, as seen in pursuits like String Theory, suggests changes in natural constants. This interdisciplinary effort aims to redefine our understanding of the gravitational constant "G," emphasizing its eternal constancy while connecting the domains of General Relativity and Quantum Physics. This abstract captures the essence of groundbreaking research at the crossroads of light, gravity, and theoretical frameworks in astronomy and astrophysics, offering exciting potential for transformative discoveries at the forefront of optical and gravitational sciences.